2018
DOI: 10.1024/0301-1526/a000716
|View full text |Cite
|
Sign up to set email alerts
|

Treating great and small saphenous vein insufficiency with histoacryl in patients with symptomatic varicose veins and increased risk of surgery

Abstract: We demonstrated that treating insufficient saphenous veins with modified histoacryl application brought a relief from symptoms of venous insufficiency and that the efficiency of this technique is comparable to commonly used methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…These injuries increase patient distress and prolong postoperative active and hospitalization. SEPS is performed by endoscopic ligation of the deep subfascial communicating branch vein, and its precise positioning can reduce unnecessary trauma, thereby shortening the time for patients to get out of postoperative active and hospitalization stay after surgery [ 13 , 14 ]. It is found that SEPS can reduce the occlusion rate of the incidence of ulcers in patients after surgery.…”
Section: Related Workmentioning
confidence: 99%
“…These injuries increase patient distress and prolong postoperative active and hospitalization. SEPS is performed by endoscopic ligation of the deep subfascial communicating branch vein, and its precise positioning can reduce unnecessary trauma, thereby shortening the time for patients to get out of postoperative active and hospitalization stay after surgery [ 13 , 14 ]. It is found that SEPS can reduce the occlusion rate of the incidence of ulcers in patients after surgery.…”
Section: Related Workmentioning
confidence: 99%
“…As reported in a previous study, although cyanoacrylate is degraded in the body, its exact duration in the body and potential harms have yet to be elucidated [14]. Furthermore, a limitation of this study is that it did not incorporate an objective evaluation of the postoperative facial contour score, fixation strength and bone reduction.…”
Section: Discussionmentioning
confidence: 95%
“…Leakage of the glue during application can cause pulmonary embolism. 24 Losing a glue portion into the deep venous system is a technical failure that has to be avoided by external vein occlusion using the probe. If this is not effectively possible (obesity, compliance e.g.…”
Section: Disadvantages and Risks Of Methodsmentioning
confidence: 99%